ANALYSIS OF VOLUME LOAD CHANGES IN THE BS ZONE OF BJ MINE PT XYZ - Magfirah, Irma
PT XYZ is a copper and gold mining company that has been operating the BJ Mine since 2000. In 2020, advancements in mining at PT XYZ's BJ Mine led to changes in land excavation, affecting water management in the BS Zone. The BS Zone is part of the BJ Mine area, situated North-Northwest of the BJ Mine Pit. Water volume flows from here to the ST pond via gravity. The land excavation includes components like undisturbed (jungle area), disturbed (unreclaimed area), and reclaimed areas, each with different runoff behaviors causing varying water quantities. A potential concern is extreme rainfall causing forest diversion channel burden to overflow into the ST pond, increasing the volume load. Thus, analyzing land excavation changes and forest diversion effects on volume load in the BS Zone is crucial. Research found an average 2.01% volume load change due to runoff area variations. These changes in the BS Zone during 2023-2028 didn't significantly impact volume load, yet showed an average annual 0.55% increase. Forest diversion significantly influenced BS Zone volume load, with an average 25.5% increase from the total volume load.